Incidence and associated factors of perioperative hypothermia in adult patients at a university-based, tertiary care hospital in Thailand - Wongyingsinn M. (2023)
Background: Inadvertent perioperative hypothermia is an unintentional drop in core body temperature to less than 36 °C perioperatively and is associated with many negative outcomes such as infection, a prolonged stay in a recovery room, and decreased patient comfort. Objective: To determine the incidence of postoperative hypothermia and to identify the associated factors with postoperative hypothermia in patients undergoing head, neck, breast, general, urology, and vascular surgery. The incidences of pre- and intraoperative hypothermia were examined as the intermediate outcomes. Materials and methods: A retrospective chart review was conducted in adult patients undergoing surgery at a university hospital in a developing country for two months (October to November 2019). Temperatures below 36 °C were defined as hypothermia. Univariate and multivariate analyses were used to identify factors associated with postoperative hypothermia. Results: A total of 742 patients were analyzed, the incidence of postoperative hypothermia was 11.9% (95% CI 9.7%-14.3%), and preoperative hypothermia was 0.4% (95% CI 0.08%-1.2%). Of the 117 patients with intraoperative core temperature monitoring, the incidence of intraoperative hypothermia was 73.5% (95% CI 58.8–90.8%), and hypothermia occurred most commonly after anesthesia induction. Associated factors of postoperative hypothermia were ASA physical status III-IV (OR = 1.78, 95%CI 1.08–2.93, p = 0.023) and preoperative hypothermia (OR = 17.99, 95%CI = 1.57-206.89, p = 0.020). Patients with postoperative hypothermia had a significantly longer stay in the PACU (100 min vs. 90 min, p = 0.047) and a lower temperature when discharged from PACU (36.2 °C vs. 36.5 °C, p < 0.001) than those without hypothermia. Conclusion: This study confirms that perioperative hypothermia remains a common problem, especially in the intraoperative and postoperative periods. High ASA physical status and preoperative hypothermia were associated factors of postoperative hypothermia. In order to minimize the incidence of perioperative hypothermia and enhance patient outcomes, appropriate temperature management should be emphasized in patients at high risk. Registration: Clinical Trials.gov (NCT04307095) (13/03/2020).